Analysis of the Effect of Economic Growth on Poverty Levels in Bandung - tiarafildzahrizka , tiarafildzahrizka; Pramita, Sasti; Br Damanik, Nia Natanesa; Br Nainggolan, Agnes Debora (Outline Journal of Economic Studies, 2023)
Poverty is a problem in a complex and multidimensional economy. Therefore it is necessary to find a solution to overcome or at least reduce the level of poverty. This study aims to analyze the effect of the level of economic growth on the level of poverty in the province of West Java, specifically the capital city of Bandung. The method used in this study is a simple linear regression method with Ordinary Least Square (OLS) with one dependent variable and classical assumption test. simple method is used to see how the dependent variable influences the independent variable. The results of the analysis in this study show that economic growth has no effect on the poor population in Bandung in 2011-2020, which means that the hypothesis of the effect of economic growth on the poverty rate in Bandung is acceptable.